SAT0485 What is the effect of cyclophosphamide iv pulse therapy in patients with diffuse cutaneous systemic sclerosis on skin involvement: an observational study. (12th June 2018) - Kersten, B.; den Broeder, N.; van den Hoogen, F.; van den Ende, E.; Vonk, M.
Abstract : Background: Patients with systemic sclerosis who have proximal skin involvement are classified as diffuse cutaneous systemic sclerosis (DcSSc). Patients with progressive skin involvement have worse prognosis due to internal organ involvement. Treatment options of these patients consist among others of cyclophosphamide iv pulse therapy (iv CYC). 1 Recent studies show significant improvement of skin thickening in patients treated with CYC orally, 2 but the effect of iv CYC on skin involvement remains unclear. Objectives: To examine the extent of skin involvement during 12 monthly iv CYC (750 mg/m 2 ) in DcSSc and to identify factors that predict response to therapy. Methods: Patients with DcSSc receiving iv CYC between 2004 and 2016 were included if they received at least 6 pulses. Skin involvement was accessed with the modified Rodnan Skinscore (mRSS) at baseline, month 6, 12, 24 and 36 by the same trained rheumatologist as part of routine care. Data of patients with the baseline measurement and at least one follow up measurement were included in the study. Missing mRSS data were imputed using multiple imputation by chained equation. Patients were classified as responders if the mRSS decreased at least 5 points and 25% from baseline at month 12. A prediction model for response at 12 months was created using backwards logistic regression considering baseline variables and response at 6 months as possible predictors. Results: A total of 99 patients were included. The mean improvement of mRSS over time was −4.05 (95% CI −5.53 to −2.55) (figure 1). 43% of patients had a response according to the response criteria. In univariate prediction models, baseline mRSS (OR 1.06, p=0.024), response at 6 months (OR: 37.45, p<0.001) and completed treatment (yes/no) (OR: 4.108, p=0.033), were significant predictors of response at 12 months. For the last variable it should be mentioned that some patients who did not achieve a response at month 6 did not continue iv CYC for that reason. Conclusions: This study shows that only 43% of the treated DcSSc patients experienced clinical important improvement of skin involvement following iv CYC. Response at month 6 is the best predictor for response on month 12. This could imply that at this time point, counselling about other available treatment options, should be considered in those patients. References: [1] Kowal-Bielecka O, et al. EULAR recommendations for the treatment of systemic sclerosis: a report from the EULAR Scleroderma Trials and Research group (EUSTAR). Annals of the rheumatic diseases2009;68(5):620–8. [2] Namas R, et al. Efficacy of mycophenolate mofetil and oral cyclophosphamide on skin thickness: Post-hoc analyses from the Scleroderma Lung Study I and II. Arthritis care & research2017. Disclosure of Interest: None declared